Determination of soil specific surface area by water vapor adsorption: II Dependence of soil specific surface area on clay and organic carbon content - Niskanen, Raina; Mäntylahti, Väinö (Agricultural and Food Science, 1987)
The specific surface area of 60 mineral soil samples estimated by water vapor adsorption at 20 % relative humidity ranged from 12.1 ± 3.6 to 225.1 ±18.4 m2/g. Clay (range 1—72 %) and organic carbon content (0.7—14.6 %) together explained 84 % of the variation in the surface area. The regression equation predicting the specific surface area of soil was surface area (m2/g) =2.69+ 1.23clay-% +8.69org.C-%.